A novel secure communication scheme in vehicular ad hoc networks - Wang, Neng-Wen; Huang, Yueh-Min; Chen, Wei-Ming (Computer communications, 2008)
Vehicular networks are very likely to become the most pervasive and applicable of mobile ad hoc networks in this decade. Vehicular Ad hoc NETwork (VANET) has become a hot emerging research subject, but few academic publications describing its security infrastructure. In this paper, we review the secure infrastructure of VANET, some potential applications and interesting security challenges. To cope with these security challenges, we propose a novel secure scheme for vehicular communication on VANETs. The proposed scheme not only protects the privacy but also maintains the liability in the secure communications by using session keys. We also analyze the robustness of the proposed scheme.